Pyocin inhibition of Neisseria gonorrhoeae: mechanism of action. - Morse, S A (1980)
Purified R-type pyocins (611 131) from Pseudomonas aeruginosa PA103 exhibited bactericidal activity against Neisseria gonorrhoeae. Killing of gonococci was a single-hit process requiring as few as 1 pyocin per colony-forming unit. Deoxyriboinucleic acid, ribonucleic acid, protein, and lipid syntheses were rapidly and completely inhibited. Oxygen uptake was also inhibited, but occurred after the inhibition of macromolecular synthesis. The cell lysis which occurred after pyocin inhibition of gonococcal growth was the result of endogenous gonococcal autolysin activity.